KAJIAN KEPUTUSAN PEMBELIAN KONSUMEN DI E-COMMERCE: STUDI PADA ERIGO STORE - Saputra, Aldi Tri; Hidayat, Irwan; Hurairah, Rizky Abu; Prasetyo, Johan Hendri (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
The use of e-commerce in Indonesia has grown very rapidly and continues to increase. Erigo Store has become one of the leading e-commerce platforms in Indonesia. This study aims to analyze the factors influencing purchase decisions at Erigo Store. This research uses a qualitative method through interviews and observations. The research sample consists of 27 key respondents who are Erigo Store consumers. The results of this study indicate that Indonesian e-commerce consumers tend to look for quality products at affordable prices. Positive reviews from other consumers also become an important factor that can increase consumer trust and encourage them to make purchases. This research provides valuable insights for business owners and marketers in the e-commerce market. These findings affirm that companies need to understand the importance of maintaining a balance between price and product quality to enhance consumer appeal and trust.